Baule monkeys - Claessens, Bruno 1983-; Danis, Jean-Louis (Mercatorfonds, 2016)
Straying from the traditional art canon of the delicate Baule masks and figures, Baule monkeys explores the darker side of this art form, in all its aspects. This makes it the first book to deal exclusively with the eponymous sculptures. These awe-inspiring bowl-bearing figures were physical manifestations of invisible powers, both malign and benign, and served their communities through the mediation of diviners. Using a group of remarkable figures from the Africarium collection as illustration, the book focuses on the creation, usage and form of these bowl bearers and sheds light on the cultural and ritual context in which they operated. Through extensive research, the book combines new and fascinating discoveries with all previous relations on the subject. This research is accompanied by many splendid images. Not only does the book include an original map and never before published field photos, it also contains 15 objects from the Africarium collection and 40 monkey figures from other public and private collections represented in full-page illustrations, and in smaller formats. This gives the reader a chance to see the works in great detail and from different angles